Understanding juvenile justice and delinquency - McShane, Marilyn D.; Cavanaugh, Michael R. (Praeger, an imprint of ABC-CLIO, LLC, 2016)
"Perceiving is Believing. Tracing beliefs about the causes of delinquency over time, we find that theories ranged from demons and climate variations to glandular dysfunctions and a lack of wholesome recreational activities. Around the end of World War II, the editors of the Saturday Evening Post wrote that "Sinister effects on the behavior and character of America's children constitute one of the greatest evils of this war. Statistics gathered from a number of places reveal a sharp nationwide increase in juvenile wrong-doing."1 Despite the attraction of explaining delinquency based on contemporary and powerful social events, the problem of delinquency persists, as do some of its basic themes such as the influence of family, friends, learning and economic pressures. In the Gluecks' treatise Delinquents in the Making they state that "The riddle of crime is so puzzling that to arrive at adequate explanations calls for the collaboration of many sciences."2 It is no surprise, then, that the science of criminology and criminal justice is as interdisciplinary as it is controversial"--